Urban–Rural Dichotomy of Burn Patients in Georgia and South Carolina. Issue 5 (September 2015) - Mian, Mohammad Anwarul Huq; Haque, Akhlaque; Mullins, Robert Fred; Fiebiger, Barbara; Hassan, Zaheed
<x xml:space="preserve">Abstract</x> This study uses a 4-year (2006–2009) cross-section of epidemiological burn injury data from Georgia and South Carolina. The results from the study show that the burn patients from rural areas differ from their urban counterparts in terms of relative burn injury incidence. Younger population groups that live in lower socioeconomic status communities especially in the urban areas are at a higher risk than other population groups. The differences in the types of burns in the urban–rural communities can give us further insights to the patients' association with injury sites. The presence of fewer burn injury treatment and care facilities in rural areas and the high incidence of burn in low-income communities in the urban areas should carry important policy implications for health planners. This study will enable researchers to understand the epidemiology of burn injuries at the local and national levels in the United States. It also carries important implications for using Geographic Information Systems for studying spatial distribution of burn injuries for disaster planning and mitigation of burn injuries.